Succession in highland forest fragments in south brazil: A floristic-structural and phylogenetic approach Sucessão em fragmentos florestais altomontanos no sul do brasil: Uma abordagem florístico-estrutural e filogenética - Duarte E.* (2018)
© 2018, Universidade Federal de Santa Maria. All rights reserved.We aimed to describe the floristic-structural organization, the richness and the phylogenetic structure of tree components in highland forest fragments in different successional stages, at São Joaquim National Park, in the municipality of Urubici, Santa Catarina state. Three fragments were selected, two in an advanced successional stage and one in an initial successional stage, being each one evaluated by 20 10 x 10 m sampling plots, allocated as 20 x 100 m transects. All trees with dbh ≥ 5 cm were identified and measured. The data were analyzed through rarefaction, multivariate ordination, indicator species analysis and phylogenetic structure metrics. There was no relationship between the richness and the successional stage, once the studied areas did not differ in relation to the number of species. The floristic-structural organization was influenced by the interaction between the successional stage and the environmental differences among areas. Phylogenetic clustering of species was observed in the initial successional stage area and random phylogenetic pattern was observed in advanced successional stage areas. The results indicated independent variation in richness in relation to successional phase and, that the forest succession influenced the floristic-structural composition and phylogenetic structure of the study areas.